2020
DOI: 10.1186/s12985-020-01337-7
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen new nucleotide substitutions in variants of human papillomavirus 18 in Korea

Abstract: High-risk human papillomavirus (HPV) infection is an essential factor for the development of cervical cancer. HPV18 is the second most common carcinogenic HPV type following HPV16, but the lineages of HPV18 have been less well studied than those of HPV 16. The purpose of this study was to analyze the nucleotide variants in the E6, E7, and L1 genes of HPV18, to assess the prevalence of HPV18 variants in Korea and to explore the relationship between HPV18 genetic variants and the risk for cervical cancer. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…In our population, eight substitutions were found in HPV18 variants which were not previously reported in the country. Following further examination, we found these mutations previously reported by Korean researchers [ 18 ], a finding that supports the geographical distribution of HPV lineages. Previous studies have found that HPV18 lineage B could be associated with a higher risk of CC than lineage A, and a higher risk of persistence and progression [ 60 , 66 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our population, eight substitutions were found in HPV18 variants which were not previously reported in the country. Following further examination, we found these mutations previously reported by Korean researchers [ 18 ], a finding that supports the geographical distribution of HPV lineages. Previous studies have found that HPV18 lineage B could be associated with a higher risk of CC than lineage A, and a higher risk of persistence and progression [ 60 , 66 ].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, HPV16 sublineages A3, A4, and D have been reported to be associated with higher risks of CC [ 14 16 ]. Conversely, most studies do not support any of HPV18 lineages or sublineages carrying a higher risk of cancer compared to others [ 17 , 18 ]. However, these findings were not replicated globally and the inconsistent results highlight the necessity of further studies on the distribution of HPV16/18 lineages and sublineages in different regions and their oncogenicity considering ethnicity.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, sublineage A1 comprised 91.7%. Fifteen new nucleotide substitutions were identified among 44 nucleotide substitutions from which six substitutions at positions 317, 443, 5467, 5560, 6462, and 6823 resulted in amino acid changes in E6 including F71L, N113K; L1: H13R, H44P, A345T, and N465S [ 32 ]. Among the reference sublineages, A3 was reported to harbor amino acid changes from E to G at position 43 in contrast to other HPV18 sublineages.…”
Section: Discussionmentioning
confidence: 99%